Non-invasive and transdermal measurement of blood uric acid level in human by electroporation and reverse iontophoresis - Chih-Kuei Lee (Dove Medical Press, 2010)
Chih-Kuei Lee1, Congo Tak-Shing Ching2–4, Tai-Ping Sun2,3, Chun-Lang Tsai2, Wei Huang5, Hsin-Hung Huang6, Jen-Fu Kuo7, Li-Hang Lai6, Mei-Ya Chien8, Hsin-Hui Tseng9, Hui-Tzu Pan10, Shiow-Yuan Huang4, Hsiu-Li Shieh3, Wei-Hao Liu2, Chia-Ming Liu2, Hsin-Wei Huang21Hopkins Health Management Center, Puli Christian Hospital, Nantou, Taiwan, Republic of China; 2Graduate Institute of Biomedicine and Biomedical Technology, National Chi Nan University, Nantou, Taiwan, Republic of China; 3Department of Electrical Engineering, National Chi Nan University, Nantou, Taiwan, Republic of China; 4Department of Photonics and Communication Engineering, Asia University, Taichung, Taiwan, Republic of China; 5Division of Immunology and Rheumatology, Puli Christian Hospital, Nantou, Taiwan, Republic of China; 6Family Medical Department, Puli Christian Hospital, Nantou, Taiwan, Republic of China; 7Division of Endocrinology and Metabolism, Puli Christian Hospital, Nantou, Taiwan, Republic of China; 8Nutrition Department, Puli Christian Hospital, Nantou, Taiwan, Republic of China; 9Aboriginal Health Care, Puli Christian Hospital, Nantou, Taiwan, Republic of China; 10Department of Medical Research and Education, Puli Christian Hospital, Nantou, Taiwan, Republic of ChinaAbstract: The aim of this study was to find out the optimum combination of electroporation (EP) and reverse iontophoresis (RI) on noninvasive and transdermal determination of blood uric acid level in humans. EP is the use of high-voltage electric pulse to create nano-channels on the stratum corneum, temporarily and reversibly. RI is the use of small current to facilitate both charged and uncharged molecule transportation across the skin. It is believed that the combination of these two techniques has additional benefits on the molecules’ extraction across the human skin. In vitro studies using porcine skin and diffusion cell have indicated that the optimum mode for transdermal uric acid extraction is the combination of RI with symmetrical biphasic direct current (current density = 0.3 mA/cm2; phase duration = 180 s) and EP with 10 pulses per second (voltage = 100 V/cm2; pulse width = 1 ms). This optimum mode was applied to six human subjects. Uric acid was successfully extracted through the subjects’ skin into the collection solution. A good correlation (r2 = 0.88) between the subject’s blood uric acid level and uric acid concentrations in collection solutions was observed. The results suggest that it may be possible to noninvasively and transdermally determine blood uric acid levels.Keywords: Reverse iontophoresis, electroporation, uric acid, monitoring, noninvasive, transdermal